Local Culture Integration in IPAS Learning: Supporting Indonesian Primary Students’ Well-Being toward SDG 4 - Muhammad Idris Maas Zaid; Mustapa Ahmad (Journal of Contemporary Gender and Child Studies, 2026)
Prior studies on science education in Indonesia have predominantly examined curriculum design, pedagogical strategies, and technology-based interventions; however, few have explored how the integration of local cultural values into Natural and Social Science (IPAS) learning specifically shapes the wellbeing of lower primary students (Grades 1-3) in culturally diverse Indonesian contexts. This study addresses that gap by examining how teachers integrate Javanese and broader Indonesian local cultural elements into IPAS instruction and the consequent effects on students' academic wellbeing and sense of belonging. Employing a qualitative phenomenological approach, data were collected through semi-structured interviews with three classroom teachers and one principal, classroom observations, document analysis, and focus group discussions involving ten students from two schools in the Yogyakarta Special Region. Thematic analysis revealed four interconnected themes: (1) cultural embodiment of science concepts through local artefacts and ecological knowledge; (2) enhanced student wellbeing via cultural familiarity; (3) the teacher as cultural mediator; and (4) alignment with SDG 4 targets for inclusive and quality education. Findings indicate that culturally embedded IPAS learning not only reduces science anxiety among early-grade students but also strengthens their identity, curiosity, and holistic development. This study contributes a culturally grounded pedagogical framework for IPAS instruction in Indonesian primary schools, with practical implications for curriculum designers, teacher educators, and policymakers pursuing SDG 4 commitments.